Environmental awareness of artisanal fishers and their participation in co-management in Manjung District, Malaysia - Alias, Ahmad Faisal (2014)
The research was conducted to measure the level of environmental awareness, knowledge, attitudes, and their perceptions of and the willingness to participate in community based fishery co-management program of artisanal fishers in the district of Manjung, Perak. The main research instrument is a face-to-face interview survey form. The respondents are 268 sampled (33.3 percent through stratified sampling method) coastal fishers holding the Class A license, who primarily operates small fishing boats within five nautical miles from shore and using traditional fishing methods. A series of surveys were conducted at selected fishing jetties and the district’s fisheries department offices. The research employs a quantitative statistical analysis approach. The analyses found that the mean environmental awareness level is ‘Medium’ (Mean = 2.84; SD = 0.98) and is significantly correlated only to their level of education (r = 0.159, n = 268, p < 0.005). Their main sources of environmental information and knowledge are the television, newspaper and radio. Only 39.9 percent of the respondents reported that they were provided information regarding the environment form the authorities and that the authorities are not doing a good job at providing the information. The respondents also reported some degrees of ‘Medium’ environmental knowledge (Mean = 2.96) and knowledge of environmental concepts (Mean = 2.70; SD = 0.74) and also ‘Medium’ pro-protective attitude towards the environment (Mean NEP score = 3.22; 53.3 summative pro-NEP score). However, their environmental awareness, knowledge and attitude are critically undermined by the pro-Dominant Social Paradigm (DSP) worldviews and attitude, as revealed by the factor analyses of their environmental knowledge and New Ecological Paradigm (NEP) scale. This fact would negatively affect their perception and behavior towards the environment and their motivation to participate in fishery resource co-management programs. Therefore, it is highly recommended that artisanal fishers be given more direct access to environmentally related information so that the influence of the DSP could be reversed and they would be more receptive towards and to actively participate in community-based fishery resource co-management programs. This can be achieved through direct and indirect methods such as having short courses or briefings, distribution of printed information or handouts and the use of mobile or other information and communication technologies (ICTs). Positive environmental awareness and attitudes can be enhanced through direct and indirect learning experience. Interest in co-management could also be encouraged through long term formal and informal information delivery methods and environmental education process and strategies at all levels.